Prophetic Mediums: Channeling the Holy Spirit(s) - Crace, Benjamin D. (2024)
This article seeks to develop an accommodationist theology of prophetic mediumship that critically incorporates ancestral presences. It argues that ancestral presence in the practice of prophecy can be supported by non-Western and non-Protestant theologies, scriptural evidence, experience, and the ecumenical church tradition. It suggests that mediumship is a helpful way of thinking about the prophetic while also maintaining a pluralistic pneumatology informed by intercultural theology. Such a theology, it is argued, can underwrite practice in which the experiential presence of holy spirits intensifies the evangelical proclamation of Christ’s victory over death and sin.
Keywords: Ancestors; Intercultural Theology; Mediumship; plural pneumatology; Prophecy